The Application of Contrast Media for In Vivo Feature Enhancement in X-Ray Computed Tomography of Soil-Grown Plant Roots. (21st March 2017) - Keyes, Samuel D.; Gostling, Neil J.; Cheung, Jessica H.; Roose, Tiina; Sinclair, Ian; Marchant, Alan
Abstract: The use of in vivo X-ray microcomputed tomography ( μ CT) to study plant root systems has become routine, but is often hampered by poor contrast between roots, soil, soil water, and soil organic matter. In clinical radiology, imaging of poorly contrasting regions is frequently aided by the use of radio-opaque contrast media. In this study, we present evidence for the utility of iodinated contrast media (ICM) in the study of plant root systems using μ CT. Different dilutions of an ionic and nonionic ICM (Gastrografin 370 and Niopam 300) were perfused into the aerial vasculature of juvenile pea plants via a leaf flap ( Pisum sativum ). The root systems were imaged via μ CT, and a variety of image-processing approaches used to quantify and compare the magnitude of the contrast enhancement between different regions. Though the treatment did not appear to significantly aid extraction of full root system architectures from the surrounding soil, it did allow the xylem and phloem units of seminal roots and the vascular morphology within rhizobial nodules to be clearly visualized. The nonionic, low-osmolality contrast agent Niopam appeared to be well tolerated by the plant, whereas Gastrografin showed evidence of toxicity. In summary, the use of iodine-based contrast media allows usually poorly contrasting root structures to be visualized nondestructively using X-ray μ CT. In particular, the vascular structures of roots and rhizobial nodules can be clearly visualized in situ .